2019
DOI: 10.1055/a-0846-0775
|View full text |Cite
|
Sign up to set email alerts
|

Safety, efficacy, and removability of a fully covered multi-hole metal stent in a swine model of hilar biliary stricture: a feasibility study

Abstract: Background and study aims Use of fully covered self-expandable metal stents (FCSEMS) for biliary drainage of malignant hilar biliary strictures is limited because of risk of cholangitis due to side branch obstruction. The aim of this study was to evaluate the safety and efficacy of unilateral placement of a multi-hole FCSEMS (FCSEMS-MH), which had a 2.5-mm hole in the center of the membrane on each cavity, in a swine model of hilar biliary stricture. Materials and methods Six female mini pigs were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In cases of benign strictures, the MHSEMS can also be easily removed. For example, MHSEMS were inserted in six mini pigs with artificial hilar biliary strictures; after 4 wk, all stents were easily and safely taken out[6]. For one of our studied cases, a MHSEMS was used for uncontrolled post-endoscopic sphincterotomy bleeding and was safely removed after 2 wk.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of benign strictures, the MHSEMS can also be easily removed. For example, MHSEMS were inserted in six mini pigs with artificial hilar biliary strictures; after 4 wk, all stents were easily and safely taken out[6]. For one of our studied cases, a MHSEMS was used for uncontrolled post-endoscopic sphincterotomy bleeding and was safely removed after 2 wk.…”
Section: Discussionmentioning
confidence: 99%
“…22 Other studies have equally reported that segmental strictures form in the region where RFA has been performed. [23][24][25] Thus, biliary stent placement after RFA is still recommended to maintain biliary drainage. Accordingly, the goal of endobiliary RFA is to improve stent (A) (B)…”
Section: Role Of Endoscopic Rfa In the Treatment Of Mbomentioning
confidence: 99%
“…For example, when the stricture length is short, effective ablation cannot be performed because the electrodes do not make sufficient contact with the tissue or cause damage to the normal bile ducts. 37,80,81 Ablation of a nonstenotic bile duct causes scar stenosis, [22][23][24][25] which means that unnecessary ablation may expand the stenotic area and increase the risk of stent occlusion. In recent years, four types of ELRA catheters with different ablation lengths have been developed, which may mitigate this problem.…”
Section: Future Prospects Of Endoscopic Rfamentioning
confidence: 99%